Caring for children in pediatric intensive care units: An observation study focusing on nurses' concerns. (August 2013) - Mattsson, Janet; Forsner, Maria; Castrén, Maaret; Arman, Maria
Children in the pediatric intensive care unit are indisputably in a vulnerable position, dependent on nurses to acknowledge their needs. It is assumed that children should be approached from a holistic perspective in the caring situation to meet their caring needs. The aim of the study was to unfold the meaning of nursing care through nurses' concerns when caring for children in the pediatric intensive care unit. To investigate the qualitative aspects of practice embedded in the caring situation, the interpretive phenomenological approach was adopted for the study. The findings revealed three patterns: medically oriented nursing— here, the nurses attend to just the medical needs, and nursing care is at its minimum, leaving the children's needs unmet; parent-oriented nursing care —here, the nursing care emphasizes the parents' needs in the situation, and the children are viewed as a part of the parent and not as an individual child with specific caring needs; and smooth operating nursing care orientation— here, the nursing care is focused on the child as a whole human being, adding value to the nursing care. The conclusion drawn suggests that nursing care does not always respond to the needs of the child, jeopardizing the well-being of the child and leaving them at risk for experiencing pain and suffering. The concerns present in nursing care has been shown to be the divider of the meaning of nursing care and need to become elucidated in order to improve the cultural influence of what can be seen as good nursing care within the pediatric intensive care unit.